2022
DOI: 10.4103/joco.joco_94_22
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Degeneration Imaging with Optical Coherence Tomography Angiography

Abstract: Purpose: To describe a series of cases of lattice degeneration of the retina imaged with optical coherence tomography angiography (OCTA). Methods: Four eyes of four patients were included and evaluated with green reflectance using a confocal scanning laser ophthalmoscopy and OCTA. In each case, the microcirculation of the retina and choriocapillaris within the lesion, as well as choroidal thickness beneath the lesion, were assessed. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…We found that combining B-scan US and eye-steering UWFI may be always preferred regardless of the number, type, and location of retinal tears. For atrophic holes, UWFI also showed comparable sensitivity to the gold standard, probably because atrophic holes are often accompanied by retinal degeneration 21,22 that provides a valuable clue in UWFI. Although B-scan US performed worse for the relatively flat atrophic type, it showed comparable sensitivity to the gold standard for horseshoe tears, probably because these tears always present abnormal echoes at the vitreoretinal interface, which can be easily noticed by ultrasonography.…”
Section: Discussionmentioning
confidence: 92%
“…We found that combining B-scan US and eye-steering UWFI may be always preferred regardless of the number, type, and location of retinal tears. For atrophic holes, UWFI also showed comparable sensitivity to the gold standard, probably because atrophic holes are often accompanied by retinal degeneration 21,22 that provides a valuable clue in UWFI. Although B-scan US performed worse for the relatively flat atrophic type, it showed comparable sensitivity to the gold standard for horseshoe tears, probably because these tears always present abnormal echoes at the vitreoretinal interface, which can be easily noticed by ultrasonography.…”
Section: Discussionmentioning
confidence: 92%
“…At the same time, large white vessels are still perfused by means of OCTA. 25 This fact, as well as the scattered pattern of vessel loss around the lesion, suggests that vascular changes could have secondary character since even on high-resolution images no regularity in the distribution of retinal non-perfusion is observed ( Figure 6 ). Due to the loss of RPE, visualization of the choriocapillaris is enhanced within the LD region.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…OCTA produces readable images in a significant proportion of LD eyes, mostly in those with midperiphery lesions. 25 , 32 Although this helps in evaluation of some details of anatomical relationships within the lesion, the clinical significance of this imaging is less important than structural OCT, due to the complexity OCTA in retinal periphery.…”
Section: Imaging Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have visualized and analyzed anatomic changes of lattice degeneration and adjacent vitreous using spectral domain optical coherence tomography (SD-OCT) and OCT angiography. However, these devices can only capture central retina, peripheral lattice degeneration could not be characterized [ 3 , 10 13 ]. Ultra-widefield (UWF) swept-source OCT (SS-OCT) system is a novel device that combines UWF scanning laser opthalmoscope (SLO) with a navigated SS-OCT (Silverstone, Nikon Healthcare Japan Inc).…”
mentioning
confidence: 99%